M6A facilitates YTHDF‐independent phase separation. Issue 2 (4th December 2019) - Liu, Si‐Yu; Feng, Yi; Wu, Jun-Jie; Zou, Ming-Li; Sun, Zi-Li; Li, Xia; Yuan, Feng‐Lai
Abstract: N6‐methyladenosine (m 6 A) is one of the most abundant messenger RNA (mRNA) modifications in eukaryotes and is involved in various key processes of RNA metabolism. In this issue of Nature, Ries et al (2019) described the fundamental features of m6A modification of mRNAs in regulating the composition of the phase‐separated transcriptome on the basis of number and distribution, and provide strong evidence that m6A plays a role in regulating phase separation in cells.